Histories of Conquest, Diversity, and Social Cohesion in Former Colonial Europe. (October 2019) - Ponce, Aaron
Research has overlooked the influence of countries' colonizing histories on how present-day diversity shapes forms of social cohesion. Ethnic boundary theories suggest that legacies of colonizing external territories could strengthen the boundaries that separate natives from foreign migrants. Alternatively, colonization could simply give countries greater experience with foreign populations over time, thus diffusing boundaries through sustained integration processes. This article investigates how history shapes diversity's influence on horizontal and vertical forms of social cohesion: support for welfare to reduce hierarchical class differences and trust of the generalized other. Using 2002 to 2014 European Social Survey and country history data, I find that while diversity often directly reduces both welfare support and trust, histories of conquest moderate this relationship. Specifically, diversity's negative influence on social cohesion outcomes gradually diminishes with the occupation of foreign territories, in contrast to their colonization. While prior research emphasizes diversity as a straightforward negative force, current findings show that it is shaped by historical episodes of symbolic boundary making.